Role of N-Terminal Pro-brain Natriuretic Peptide in the Early Diagnosis of Neonatal Sepsis - Okur, Nilufer; Buyuktiryaki, Mehmet; Uras, Nurdan; Oncel, Mehmet Yekta; Halil, Halid; Isık, Sehribanu; İpek, Mehmet Sah; Canpolat, Fuat Emre; Oguz, Serife Suna (Journal of Pediatric Infectious Diseases, 2019)
Objective Sepsis is one of the most significant contributors to mortality and morbidity in the neonatal population. The need to find specific biomarkers that provide meaningful information about the diagnosis of sepsis is still ongoing. This study aimed to investigate the utility of N-terminal pro-brain natriuretic peptide (NT-proBNP) as a diagnostic biomarker in newborn infants with late-onset sepsis.Methods A prospective, observational study was conducted in the neonatal intensive care unit between July 2016 and January 2017. The patients suspected of having late-onset sepsis and meeting the selection criteria were included in the study, and serial measurements of white blood cell count, serum C-reactive protein (CRP), plasma interleukin (IL) 6, and whole blood NT-proBNP levels were performed.Results The study included 87 patients diagnosed with sepsis and 35 control patients. The median NT-proBNP levels were higher in septic patients (58 [22–169] vs. 14 [7–21]; p < 0.001), showing a significant correlation with CRP and IL-6 levels (r = 0.327, p < 0.01 and r = 0.216, p < 0.05, respectively). The optimal diagnostic cutoff value for differentiating sepsis was 27.5 pg/mL. Predictive parameters of NT-proBNP, such as sensitivity (72%) and specificity (86%), were comparable to those of CRP and IL-6 for the early diagnosis of sepsis in neonates.Conclusion Plasma NT-proBNP levels were higher in septic neonates, and the predictive values were comparable to those of CRP and IL-6. However, these values were not high enough to make it a reliable diagnostic biomarker for identifying neonates in the early stages of sepsis.
Keywords: preterm; sepsis; proBNP